TRANSFORMATION OF THE PRACTICE OF GIVING 'LIN WELIN LETO WOTER' IN KROWE ETHNIC MARRIAGES: ANALYSIS OF CAUSAL FACTORS AND COMMUNITY RESPONSE - Siki, Renhat Marlianus; Suastika, I Made; Banda, Maria Matildis; Puspawati, Luh Putu (E-Journal of Cultural Studies; Vol 17 No 2 (2024): Volume 17 Number 2 May 2024, 2024)
This research explores the transformation of the practice of giving "Lin Welin Leto Woter" in Krowe ethnic marriages in Sikka Regency, East Nusa Tenggara, Indonesia, examining the influence of ideological, social, and material factors. Using qualitative methodology, data were collected through observation, interviews, and document analysis. The results reveal ideological shifts driven by modernity and globalization, social tensions triggered by manipulation within the community, and economic impacts driving adaptation. Despite facing challenges, the Krowe community demonstrates resilience by incorporating personal symbols and adjusting practices. Traditional terms persist alongside new practices, reflecting cultural continuity. From a theoretical perspective, these practices reflect the flexibility of cultural symbols, inviting further investigation. In conclusion, the Krowe community's response reaffirms their ability to navigate change while preserving cultural identity, suggesting avenues for further research and recommendations to support cultural preservation. Keywords : cultural transformation, ideological shifts, Krowe ethnic marriages, resilience, social tensions